Efektifitas Penerapan Teknik Ecoprint untuk pengembangan kemampuan Sains pada Anak Usia Dini - Ummah, Imrotul; Fitri, Ruqoyyah (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Introducing science in early childhood is about developing critical thinking skills, curiosity and the curiosity of finding answers through fun experimental activities. Ecoprint activities are one of the effective and fun ways to do this. Ecoprint is a way of decorating fabrics with different plants and taking advantage of their natural colors. The purpose of this study was to determine the effectiveness of the application of ecoprint techniques for the development of science skills in Early Childhood. This study uses a descriptive approach with a qualitative approach. Qualitative research is research that focuses on descriptive aspects as a whole. This means that the results of the study are described in detail and in context. Data analysis techniques include data reduction, data presentation, and data validation. From the results of the study it can be concluded that there are five themes related to children's understanding of science concepts obtained through Ecoprint activities including (1) recognizing colors and pigments in nature, themes that appear children recognize and name colors created with Ecoprint. (2) texture and shape of leaves emerging themes: children learn to recognize various textures and shapes of leaves through direct observation. (3) color extraction process of emerging themes: children understand that colors can be picked up by hitting or pressing leaves (4) biodiversity of emerging themes: children learn about biodiversity through the different types of leaves used. (5) developing creativity emerging themes: Ecoprint activities stimulate children's creativity. Children get creative when arranging leaves to create unique patterns